Rekam Medis Sebagai Alat Bukti Menurut Hukum - Susi Hadidjah, Suhartini dan Beta Ahlam Gizela (Berita Kedokteran Masyarakat (BKM), 2004)
Background: Treatment of victims from any violations, such as accident, crime, and human right violations, often held in non standard protedure. As the result, evidence from those cases often been managed as a common patient. Every day at least 7 request letters for the medical report (for justice) from investigator come to Medical Record Department of Sardjito Hospital. To fulfil the request doctor or hospital must take data from medical record. By the way, it is clear that medical record is very important in hospital documentation. Objective: This study was aimed at reminding the doctor that medical record was important as medical proofing in a court.Methods: This was based on reference study and medico-legal cases management experience. Results: Health Ministry Regulation No.749a/1989 describe, medical record was a document of patient identity, examination, treatment, and other services to the patient in medical facilities. In a case of violations in which there is human victim that is not managed as an evidence, medical proofing for justice is arranged based on medical record. The medical report from examination request by investigator called visum et repertum. The medical report from examination request by patient called surat keterangan medis". Doctor in his duty must do carefully, make good documentation, and report his medical finding medic-objectively, that can be checked scientifically. Conclusion: Medical record as an evidence was needed to make a case become clear in law point of view. Medical record as a documentation of medical examination must be clear, detail, and complete, so it can be checked scientifically.Keywords: medical record, proofing, violation